The Neuroglial Dialog Between Cannabinoids and Hemichannels - Labra, Valeria C.; Santibáñez, Cristian A.; Gajardo-Gómez, Rosario; Díaz, Esteban F.; Gómez, Gonzalo I.; Orellana, Juan A. (Frontiers in Molecular Neuroscience, 2018)
The formation of gap junctions was initially thought to be the central role of connexins, however, recent evidence had brought to light the high relevance of unopposed hemichannels as an independent mechanism for the selective release of biomolecules during physiological and pathological conditions. In the healthy brain, the physiological opening of astrocyte hemichannels modulates basal excitatory synaptic transmission. At the other end, the release of potentially neurotoxic compounds through astroglial hemichannels and pannexons has been insinuated as one of the functional alterations that negatively affect the progression of multiple brain diseases. Recent insights in this matter have suggested encannabinoids (eCBs) as molecules that could regulate the opening of these channels during diverse conditions. In this review, we discuss and hypothesize the possible interplay between the eCB system and the hemichannel/pannexon-mediated signaling in the inflamed brain and during event of synaptic plasticity. Most findings indicate that eCBs seem to counteract the activation of major neuroinflammatory pathways that lead to glia-mediated production of TNF-α and IL-1β, both well-known triggers of astroglial hemichannel opening. In contrast to the latter, in the normal brain, eCBs apparently elicit the Ca2+-activation of astrocyte hemichannels, which could have significant consequences on eCB-dependent synaptic plasticity.